A gene family required for human germ cell development evolved from an ancient meiotic gene conserved in metazoans - Xu, Eugene Yujun (The National Academy of Sciences, 2001)
The Deleted in AZoospermia (DAZ) genes encode potential RNA-binding proteins that are expressed exclusively in prenatal and postnatal germ cells and are strong candidates for human fertility factors. Here we report the identification of an additional member of the DAZ gene family, which we have called BOULE. With the identification of this gene, it is clear that the human DAZ gene family contains at least three members: DAZ, a Y-chromosome gene cluster that arose 30–40 million years ago and whose deletion is linked to infertility in men; DAZL, the “father” of DAZ, a gene that maps to human chromosome 3 and has homologs required for both female and male germ cell development in other organisms; and BOULE, a gene that we propose is the “grandfather” of DAZ and maps to human chromosome 2. Human and mouse BOULE resemble the invertebrate meiotic regulator Boule, the proposed ortholog of DAZ, in sequence and expression pattern and hence likely perform a similar meiotic function. In contrast, the previously identified human DAZ and DAZL are expressed much earlier than BOULE in prenatal germ stem cells and spermatogonia; DAZL also is expressed in female germ cells. These data suggest that homologs of the DAZ gene family can be grouped into two subfamilies (BOULE and DAZL) and that members of the DAZ family evolved from an ancestral meiotic regulator, Boule, to assume distinct, yet overlapping, functions in germ cell development.